Manajemen Pendidikan Karakter Dari Sudut Pandang Islam - Sabiqun Khoirot; M. Fathi El Madani; Bayu Ma’ruf Qoustaulani (CV. Syntax Corporation Indonesia, 2021)
Management is the science of using other people's help to achieve goals effectively, which means that help can be given through the help of others. In the form of thoughts and energy, it can also be intuition. Education is essentially an effort to support and guide the thoughts and nature of each person. The aim is to ensure that education develops according to the character education of the Prophet Muhammad to achieve the desired goal. Therefore, Islamic education related to Islam is a science that can guide, direct and develop. The method used in this research is qualitative method. The success of character education from an early age is to become a role model. To optimize the management of student character education, teachers must be Fathonah, Shidiq, Amanah, and Tabligh.